2016
DOI: 10.1242/bio.021402
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone regulates shoot development through a core signalling pathway

Abstract: Strigolactones are a recently identified class of hormone that regulate multiple aspects of plant development. The DWARF14 (D14) α/β fold protein has been identified as a strigolactone receptor, which can act through the SCFMAX2 ubiquitin ligase, but the universality of this mechanism is not clear. Multiple proteins have been suggested as targets for strigolactone signalling, including both direct proteolytic targets of SCFMAX2, and downstream targets. However, the relevance and importance of these proteins to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 78 publications
(180 reference statements)
3
101
0
Order By: Relevance
“…On the one hand, strigolactones repress outgrowth of axillary buds by inducing the gene expression of specific TCP transcription factors in the buds, such as BRANCHED 1 ( BRC1 ) (Braun et al ; Dun et al ), and on the other hand, they can inhibit branching by triggering the removal of the PIN‐FORMED 1 (PIN1) auxin efflux proteins from the plasma membrane (Bennett et al ; Crawford et al ; Shinohara et al ). Both pathways probably act in parallel, because tir3‐1 mutant plants with a deficient PIN1 accumulation have no increased BRC1 expression levels and brc1‐2brc2‐1 double mutants have no altered PIN1 distribution or auxin flow (Bennett et al ). In addition to branching inhibition, an even more general role for strigolactones has been suggested in the shoot, such as branch angle influence, leaf margin serrations, internode elongation, leaf senescence and secondary growth processes (Gomez‐Roldan et al ; Umehara et al ; Agusti et al ; de Saint Germain et al ; Lauressergues et al ; Sang et al ; Yamada et al ; Ueda & Kusaba ).…”
Section: Strigolactones Versus Karrikin(‐like)s Let the Game Beginmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, strigolactones repress outgrowth of axillary buds by inducing the gene expression of specific TCP transcription factors in the buds, such as BRANCHED 1 ( BRC1 ) (Braun et al ; Dun et al ), and on the other hand, they can inhibit branching by triggering the removal of the PIN‐FORMED 1 (PIN1) auxin efflux proteins from the plasma membrane (Bennett et al ; Crawford et al ; Shinohara et al ). Both pathways probably act in parallel, because tir3‐1 mutant plants with a deficient PIN1 accumulation have no increased BRC1 expression levels and brc1‐2brc2‐1 double mutants have no altered PIN1 distribution or auxin flow (Bennett et al ). In addition to branching inhibition, an even more general role for strigolactones has been suggested in the shoot, such as branch angle influence, leaf margin serrations, internode elongation, leaf senescence and secondary growth processes (Gomez‐Roldan et al ; Umehara et al ; Agusti et al ; de Saint Germain et al ; Lauressergues et al ; Sang et al ; Yamada et al ; Ueda & Kusaba ).…”
Section: Strigolactones Versus Karrikin(‐like)s Let the Game Beginmentioning
confidence: 99%
“…In addition to branching inhibition, an even more general role for strigolactones has been suggested in the shoot, such as branch angle influence, leaf margin serrations, internode elongation, leaf senescence and secondary growth processes (Gomez‐Roldan et al ; Umehara et al ; Agusti et al ; de Saint Germain et al ; Lauressergues et al ; Sang et al ; Yamada et al ; Ueda & Kusaba ). Strigolactone signalling during shoot development has been shown to be regulated by both MAX2 and D14 and to depend on the degradation of SMXL6,SMXL7,SMXL8 proteins, but without requirement of other previously proposed MAX2 targets, such as BRASSINOSTEROID INSENSITIVE 1‐ETHYL METHANESULFONATE‐SUPPRESSOR1 (BES1) and DELLA (Bennett et al ). Recent studies in pea and rice demonstrated that D14 is a mobile signal for fine‐tuning axillary bud outgrowth.…”
Section: Strigolactones Versus Karrikin(‐like)s Let the Game Beginmentioning
confidence: 99%
“…Although karrikins were instrumental in the discovery of KAI2 -not least because they are a potent activator of KAI2-dependent signalling, even in non-fire-prone plants -we now appreciate that KAI2 regulates some of the wide number of physiological processes that are dependent on MAX2. These include effects on seed germination and seedling development, as are well established, but effects on leaf development are also evident, at least in Arabidopsis (Waters et al 2012a(Waters et al , 2015bBennett et al 2016) (Fig. 2).…”
Section: Beyond Karrikins: What Else Does Kai2 Do?mentioning
confidence: 71%
“…D53 is another member of the SMXL family, all of which share similarity to the ClpB/HEAT SHOCK PROTEIN 100 (HSP100) class of heat shock proteins. In Arabidopsis, three D53 homologues (SMXL6, SMXL7 and SMXL8) act redundantly to mediate all tested strigolactonerelated components of MAX2 function (Soundappan et al 2015;Liang et al 2016;Bennett et al 2016). This redundancy might explain why suppressor screens for the increased shoot branching phenotype of max2 had not uncovered this protein family.…”
Section: : the Smxl Familymentioning
confidence: 99%
“…MeCLA then binds and induces conformational changes to the D14 α/β‐fold hydrolase allowing the interaction with a SKP1‐CUL1‐F‐box‐protein (SCF)‐type ubiquitin ligase complex to transmit the SL signal via proteasomal degradation of negative regulators of SL signaling. An integral component of this complex, the MAX2 leucine rich F‐box protein, seems to be involved in the ubiquitination of putative transcriptional regulators controlling most of the SL‐dependent responses characterized so far, including members of the SUPPRESSOR OF MAX2 (SMAX1) and SMAX1‐LIKE families (Bennett et al., ; Jiang et al., ; Soundappan et al., ; Wang et al., ). However, the function and exact mechanism of action of most of these target proteins are still under debate.…”
Section: Introductionmentioning
confidence: 99%